Suicide Risk Screening in Pediatric Outpatient Neurodevelopmental Disabilities Clinics. Issue 4 (15th May 2022) - Rybczynski, Suzanne; Ryan, Taylor C.; Wilcox, Holly C.; Van Eck, Kathryn; Cwik, Mary; Vasa, Roma A.; Findling, Robert L.; Slifer, Keith; Kleiner, Daniel; Lipkin, Paul H.
ABSTRACT: Objective: The purpose of this study was to describe the implementation of universal suicide risk screening in pediatric neurodevelopmental disabilities (NDD) medical clinics, analyze demographic and clinical characteristics of eligible patients, describe outcomes of positive screenings, and describe factors that influenced participation in screenings. Methods: A suicide risk screening protocol was developed and implemented for medical clinic patients aged 8 to 18 years. Registered nurses screened patients using the "Ask Suicide-Screening Questions" tool during triage. Positive screenings were referred for further assessment and mental health management. Demographics and clinical data were extracted from medical records using retrospective chart reviews. Results: During the 6-month study period, 2961 individual patients presented for 5260 screening eligible patient visits. In total, 3854 (73.3%) screenings were completed with 261 (6.8%) positive screenings noted. Screenings were declined in 1406 (26.7%) visits. Parents of children with cognitive impairments were more likely to decline screening. Clinics serving children with autism spectrum disorder had higher rates of positive screenings compared with all other clinic attendees. Seventy-two of 187 children (38.5%) with positive screenings were identified and referred to outpatient mental health referrals. Seven (2.5%) of these children required acute psychiatric treatment. Conclusion: Routine screening, identification of increased suicide risk, and referral to mental health care among children with NDD are feasible. It remains unclear whether variation in rates among youth with and without NDD may indicate true differences in suicide risk or cognitive impairments or reflect psychiatric comorbidities. High rates of declined participation may have influenced identification of children with NDD and suicide risk. Preliminary findings identified groups of children with NDD at heightened risk for suicidal ideation and behavior. Further research is needed to assess the validity of suicide risk screening tools in children with neurodevelopmental disorders.